Carbonatación acelerada de agregados finos reciclados y su influencia en mezclas de mortero (2017)
The recycled aggregates, obtained from demolition and construction works, have proven to be feasible in an economic, environmental, and technically way for its use in new construction projects, with which alongside the use of a CO2 capture technology, it can be improved the properties of said aggregates for structural applications. The present investigation evaluates some properties in a short, medium, and longtime range of mortar mixes with replacements of carbonated recycled aggregates in different proportions. The recycled aggregates were obtained in the laboratory, with means of mechanical crushing of discarded concrete cylinders without any characterization or clear origin. It was prepared a total of 10 different mixes, with replacement percentages of 0, 25 and 50%, for whom were determined some mechanical properties at 3, 28, 90 and 180 days. Comparatives analyses were done for each age along with a scanning electron microscope done at 28 days’ samples age. The results obtained, shown an improvement in the mortar compressive resistance in a linear way with the recycled aggregate concrete (RAC), also, it was obtained a lesser sorptivity and initial absorption rate, with a better mortar quality according to the ultrasonic pulse velocity tests.